ANALISIS KEMANDIRIAN PANGAN ASAL TERNAK DALAM RANGKA MEMANTAPKAN KETAHANAN PANGAN DI KABUPATEN LAMPUNG BARAT - Hasnul Abrar; Ali Khomsan; Yayat Heryatno (Food and Nutrition Society of Indonesia, 2008)
The objectives of this research were to: (1) analyze animal food supply in West Lampung District; (2) analyze ideal animal food target and; (3) analyze animal food self sufficiency. This research was conducted by using retrospective and prospective design. The primary data was collected by conducting interview and giving questionnaire to the chosen sample. The secondary data was processed by using Food Balance Sheet (FBS) software to measure animal food supply including the number and the energy and protein content. Food self sufficiency was analyzed by production-supply and import-supply ratio. The average animal food supply in 2005, 2006, and 2007 is 21 g/capita/day or 7.66 kg/capita/year, still lower than ideal supply 60 g/capita/day or 21.90 kg/capita/year. Protein supply of animal food is 2.86 g/capita/day, lower than ideal supply 4.8 g/capita/day.